The Prevalence of Hepatitis E in a Patient Cohort Presenting With Addictive Injection Behavior - Yrondi, Antoine; Salles, Juliette; Péron, Jean Marie; Sporer, Marie; Taib, Simon; Gallini, Adeline; Noilhan, Chloé; Dimeglio, Chloé; Entajan, Flora; Crequy, Marie; Izopet, Jacques; Schmitt, Laurent (Frontiers in Psychiatry, 2019)
Introduction: Hepatitis E is the most common cause of acute viral hepatitis world-wide. Seroprevalence is approximately 15% in developed countries, and 22% in France. HEV can be transmitted via transfusions and therefore possibly IV drug use. Hepatitis E serology is routinely tested in patients who seek medical advice for addictive injection behaviour at the addiction treatment, support and prevention unit of Toulouse University Hospital Centre. We assume that hepatitis E is more prevalent in patients presenting addictive injection behaviour than in the general French population. Methods: Hepatitis E serological assays (IgM and IgG) were carried out for all patients presenting addictive injection behaviour during an initial evaluation. The controls were taken from a cohort of 3,353 blood donors living in southern France and who donated blood during the first two weeks of October 2011. Results: We included 52 patients presenting addictive injection behavior and 103 healthy controls matched for age, sex, and area of residence. We found no difference between patients and controls for the prevalence of hepatitis E : patients vs healthy controls: positive IgGs: 42.31%, 95% CI [28.73% - 56.80 %] vs 43.43%, 95% CI [33.50% - 53.77 %] (p=0.89) and positive IgMs: 3.85%, 95% CI [0.47% - 13.22%] vs 4.85 %, 95% CI [0.16 % - 10.97 %] (p=0.57). Conclusion: There was no difference in HEV seroprevalence between the IV drug users and the general population, suggesting that the IV route of HEV infection is not significant in this population.